The role of size in biostability of DNA tetrahedra. Issue 34 (6th April 2023) - Vilcapoma, Javier; Patel, Akul; Chandrasekaran, Arun Richard; Halvorsen, Ken
Abstract : Biostability of different-sized DNA tetrahedra were analyzed against two nucleases and in fetal bovine serum. Results show that DNA nanostructure size can influence nuclease degradation, but suggest a complex relationship that is nuclease specific. Abstract : The potential for using DNA nanostructures for drug delivery applications requires understanding and ideally tuning their biostability. Here we investigate how biological degradation varies with size of a DNA nanostructure. We designed DNA tetrahedra of three edge lengths ranging from 13 to 20 bp and analyzed nuclease resistance for two nucleases and biostability in fetal bovine serum. We found that DNase I had similar digestion rates across sizes but appeared to incompletely digest the smallest tetrahedron, while T5 exonuclease was notably slower to digest the largest tetrahedron. In fetal bovine serum, the 20 bp tetrahedron was degraded four times faster than the 13 bp. These results show that DNA nanostructure size can influence nuclease degradation, but suggest a complex relationship that is nuclease specific.